Upaya Meningkatkan Nilai Agama Anak Usia Dini melalui Penggunaan Media Audio Visual di TK Dharma Wanita 2024/2025 - Zulbayani Zulbayani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve the development of early childhood religious values through the use of audio-visual learning media at Dharma Wanita Kindergarten, Lembah Melintang District. The background of this research departs from the low development of children's religious values which is characterized by a lack of prayer habits, regularity in prayer, and understanding of daily prayers. The type of research used is Classroom Action Research (PTK) which is carried out in two cycles with the stages of planning, implementation, observation, and reflection. The research subjects were 15 children consisting of 7 girls and 8 boys aged 4-5 years. Data were collected through observation and documentation and then analyzed descriptively. The results showed a significant increase in the development of children's religious values. In pre-action, only 7 children (46.66%) were classified as starting to develop and 8 children (53.34%) had not developed. After applying audio visual media, in cycle I there were 4 children (26.67%) developing as expected and 11 children (73.33%) began to develop. In cycle II, it increased to 9 children (60%) developing very well and 6 children (40%) developing as expected. Thus, the use of audio-visual media is proven to be effective in improving the development of religious values in early childhood.